Recovering Justice Amid Restorative Approach: Finding the Silver Lining in Asset Recovery on Corruption Crimes - Ahmad Fauzi; Ariesta Wibisono Anditya; Mohamad Noor Fajar Al Arif Fitriana (Universitas Negeri Semarang, 2025)
The criminal justice system is a judicial system that involves the police, prosecutors, courts, and correctional institutions as its sub-systems. This system adopts the interests of rights and remedies for criminals; the sharp criticism is that the criminal justice system ignores the rights and interests of victims, even though the victims suffer direct harm from a crime. The study aims to present how the restorative approach is applied to corruption crimes and how asset recovery mechanisms can contribute to the restoration of justice. The study applied legal research with a normative juridical approach. The primary and secondary data were analyzed using quantitative analysis. Acknowledged as an approach within criminology and criminal law, restorative justice facilitates communication among offenders, victims, and communities to address victims' concerns, bolster societal security, and deter the repetition of crimes. In instances of corruption, restorative justice employs asset recovery mechanisms, allowing victims to recover state financial losses and empowering communities with rights to justice.